2019
DOI: 10.3390/insects11010008
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Insecticide Netting for Protecting Tree Stems from Attack by Ambrosia Beetles (Coleoptera: Curculionidae: Scolytinae)

Abstract: Ambrosia beetles (Coleoptera: Curculionidae: Scolytinae) are destructive wood-boring insects of horticultural trees. We evaluated long-lasting insecticide netting for protecting stems against ambrosia beetles. Container-grown eastern redbud, Cercis canadensis, trees were flood-stressed to induce ambrosia beetle attacks, and deltamethrin-treated netting was wrapped from the base of the stem vertically to the branch junction. Trees were deployed under field conditions in Ohio, Virginia, Tennessee, and Mississipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…This is consistent with an earlier study that used an α-cypermethrin-based LLIN against L. serricorne and E. elutella to surround a carton of tobacco in a commercial tobacco facility (Athanassiou et al, 2019). Trees wrapped with LLIN also exhibited significantly reduced beetle attacks (Ranger et al, 2020). Another study found that LLIN reduced S. oryzae infestations of maize in mini-bag bioassays by 98-100%, however, there were varying amounts of permethrin residues on the maize (Anaclerio et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with an earlier study that used an α-cypermethrin-based LLIN against L. serricorne and E. elutella to surround a carton of tobacco in a commercial tobacco facility (Athanassiou et al, 2019). Trees wrapped with LLIN also exhibited significantly reduced beetle attacks (Ranger et al, 2020). Another study found that LLIN reduced S. oryzae infestations of maize in mini-bag bioassays by 98-100%, however, there were varying amounts of permethrin residues on the maize (Anaclerio et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…The netting has also been used as a preventative measure against pests of specialty crops and ornamental trees (Marianelli et al, 2018;Ranger et al, 2020). These studies support the idea that LLIN can be used to intercept insects prior to reaching their destination and causing damage.…”
Section: Introductionmentioning
confidence: 70%
“…When X. crassiusculus and X. germanus were caged to stems of flooded or nonflooded C. florida trees, foundresses established fungal gardens and produced offspring only in stems of flooded trees. Additional studies further support the preference of X. crassiusculus and X. germanus for thin-barked tree species subjected to flood stress, including Cercis canadanesis Linnaeus (Fabaceae), Malus domestica Borkhausen (Rosaceae), and Styrax japonicus Siebold (Styracaceae) (Frank and Ranger 2016;Ranger et al 2016Ranger et al , 2020Agnello et al 2017;Frank et al 2017;Werle et al 2019).…”
Section: Influence Of Host Qualitymentioning
confidence: 71%
“…This is consistent with an earlier study that used an α-cypermethrin-based LLIN against L. serricorne and E. elutella to surround a carton of tobacco in a commercial tobacco facility (Athanassiou et al, 2019). Trees wrapped with LLIN also exhibited significantly reduced beetle attacks (Ranger et al, 2020). Another study found that LLIN reduced S. oryzae infestations of maize in mini-bag bioassays by 98-100%, however, there were varying amounts of permethrin residues on the maize (Anaclerio et al, 2018).…”
Section: Discussionsupporting
confidence: 91%